Lack of association between CYP11B2 -344T/C polymorphism and transient ischemic attack in a Chinese population. Issue 8 (August 2020) - Fan, Jia; Shen, Yaoliang; Chen, Bo; Xu, Chunyang; Ye, Hongwei; Wang, Jian; Zhou, Wenjun; Sheng, Yuefeng; Xu, Feng; Yang, Peng
Objective: This study investigated whether the CYP11B2 -344T/C polymorphism is correlated with transient ischemic attack (TIA) susceptibility. Methods: We recruited 100 TIA patients and 100 control subjects and analyzed the CYP11B2 -344T/C polymorphism using restriction fragment length polymorphism (PCR–RFLP). Results: The frequency in TIA patients and controls was 42% compared with 48% for TT genotypes, 51% compared with 45% for TC genotypes, and 7% compared with 7% for CC genotype, respectively. Allele frequencies in TIA patients and controls were 67.5% compared with 70.5% for T-allele and 32.5% compared with 29.5% for C-allele, respectively. No association between the CYP11B2 -344T/C polymorphism and TIA was observed in all comparisons. Conclusion: Our data suggest that there was no association between the CYP11B2 -344T/C polymorphism and TIA in a Chinese population.